ALTERNATIF STRATEGI MENEKAN KESENJANGAN KEMANDIRIAN FISKAL ANTAR DAERAH DI INDONESIA - Muhammad Fachril Husain Jeddawi (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2021)
Regional autonomy in a climate of democratization of governance in the regions, with the initialmomentum of the birth of decentralized policies through Law Number 22 of 1999 concerningRegional Government which was later changed to Law Number 32 of 2004, most recently with LawNumber 23 of 2014, which had also undergone a change, the essence of which was to strengthenthe Autonomous Region. In supporting (the implementation of regional autonomy, among otherthings, adequate budget support is needed. Therefore, regional autonomy needs to be supported byregional fiscal independence. One approach used in the review of regional fiscal independence is toassess the implementation of fiscal decentralization in local governments. Fiscal decentralizationis the delegation of responsibility and authority over central expenditures and revenues to local governments. This fiscal decentralization aims to enable local governments to exercise governmentauthority, among others, with the assistance of funds from the center (balancing funds). The resultsof the review on fiscal independence show that there are 88.07% of local governments which arenot yet independent (443 of 503 local governments) and there are 93.04% of local governmentswhose status has not changed/stagnant (468 of 503 local governments).The results of the review ofthe implementation of fiscal decentralization in 4 samples of local governments show a very goodcategory, this is i shows that funds from the central government (balancing funds) are well absorbedand create dependence of local governments on these balancing funds in managing their regions.The results of the study conclude that there are several alternative strategies that can be carriedout in an effort to reduce the deficit of fiscal independence and in order to increase PAD includingintensifying and extensifying regional taxes / levies, building infrastructure that invites objectsof taxes / levies, increasing the capacity of human resources for managing PAD and performingaccurate calculations. to the potential of the region, increasing community participation to supportthe increase in PAD by using short videos / infographics, increasing and encouraging investmentand supervision from local governments in every activity carried out.